4-Phenylpyrimidine monolayer protection of a copper surface from salt corrosion. Issue 14 (15th February 2018) - Wei, N.; Jiang, Y.; Liu, Z.; Ying, Y.; Guo, X.; Wu, Y.; Wen, Y.; Yang, H.
Abstract : The efficiency of a 4-phenylpyrimidine monolayer optimally self-assembled on a copper surface against corrosion by a 3 wt% NaCl solution could reach 83.2%. Abstract : 4-Phenylpyrimidine (4-PPM) containing N heteroatoms can easily form compact and uniform layers on metallic surfaces. In this work, the protection of a copper surface from corrosion in 3 wt% NaCl by a 4-PPM layer was investigated by electrochemical impedance spectroscopy (EIS) and polarization methods. Under optimum conditions, the inhibition efficiency of a 4-PPM layer for copper corrosion reached 83.2%. Raman analysis in conjunction with calculations using density functional theory (DFT) based on the B3LYP/LANL2DZ basis set suggested that the 4-PPM molecule anchored on the copper surface via the N1 atom to construct a uniform layer.